Advanced Wired and Wireless Networks - Wysocki, Tadeusz A.; Dadej, Arek; Wysocki, Beata J. (Multimedia Systems and Applications, 2005)
ADVANCED WIRED AND WIRELESS NETWORKS brings the reader a sample of recent research efforts representative of advances in the areas of recognized importance for the future Internet, such as ad hoc networking, mobility support and performance improvements in advanced networks and protocols. In Part I, we bring ad-hoc networking closer to the reality of practical use. The focus is on more advanced scalable routing suitable for large networks, directed flooding useful in information dissemination networks, as well as self-configuration and security issues important in practical deployments. Part II illustrates the efforts towards development of advanced mobility support techniques (beyond traditional "mobile phone net") and Mobile IP technologies. The issues range from prediction based mobility support, through context transfer during Mobile IP handoff, to service provisioning platforms for heterogeneous networks. The focus of the final section concerns the performance of networks and protocols. Furthermore this section illustrates researchers' interest in protocol enhancement requests for improved performance with advanced networks, reliable and efficient multicast methods in unreliable networks, and composite scheduling in programmable/active networks where computing resources equal network performance as transmission bandwidth. ADVANCED WIRED AND WIRELESS NETWORKS is structured to meet the needs of a professional audience in industry, as well as graduate-level students in computer science and engineering.